A case series of dural venous sinus stenting in idiopathic intracranial hypertension: association of outcomes with optical coherence tomography1. (1st February 2017) - Smith, Kyle A.; Peterson, Jeremy C.; Arnold, Paul M.; Camarata, Paul J.; Whittaker, Thomas J.; Abraham, Michael G.
Abstract : Purpose/Aim : Pseudotumor cerebri or idiopathic intracranial hypertension (IIH) is characterized by increased intracranial pressure of unknown etiology. A subset of patients has shown benefit from endovascular dural venous sinus stenting (DVSS). We sought to identify a population of IIH patients who underwent DVSS to assess outcomes. Materials and Methods : A retrospective study was performed to identify IIH patients with dural sinus stenosis treated with DVSS. Outcome measures included dural sinus pressure gradients, peripapillary retinal nerve fiber layer (RNFL) thickness using optical coherence tomography and improvement in symptoms. Results : Seventeen patients underwent DVSS. Average pre- and post-intervention pressure gradients were 23.06 and 1.18 mmHg, respectively ( p < 0.0001). Sixteen (94%) noted improvement in headache, fourteen (82%) had visual improvement and all (100%) patients had improved main symptom. Of 11 patients with optical coherence tomography, 8 showed decreased RNFL thickness and 3 remained stable; furthermore, these 11 patients had improved vision with improved papilledema in 8, lack of pre-existing papilledema in 2 and stable, mild edema in 1 patient. Conclusions : Our series of patients with dural sinus stenosis demonstrated improvement in vision and reduction in RNFL thickness. DVSS appears to be a useful treatment for IIH patients with dural sinus stenosis.